Ensino na área de saúde: aproximações às estratégias de ensino-aprendizagem dos professores de Terapia Ocupacional - Ramalhão, Annie Betune [UNIFESP] (2006)
The objective of this research was identify and analyze the practical conceptions used by professors of Occupational Therapy of the state of São Paulo in the implementation of teach-learning strategies in the referring curricular component Gerontology/Geriatry offered in the courses of Occupational Therapy. We construct the theoretical base of the research in three areas: 1) the discussion of the faculty teach-learning practices according to the centrality that strategies discharge; in the professor, the pupil or the interrelation between them; 2) a historical retaken of the Occupational Therapy education in Brazil and the Curricular policies; 3) the concern of the gerontology and geriatry education in health education specifically in the Occupational Therapy. In the methodology resorted we consider the relation with the world where they got into and the understanding of meaning that the respondent give to their practices, being this research characterized as qualitative. Five universities had been part of this study, which seven professors responsible for the curricular component who had answered to a questionnaire and had granted an interview had been part of this research we also consult the professor teaching design and the register of the privileged curricular component. The data had been analyzed using the thematic analysis from the following orienting core: curricular component characteristics, professor profile, conceptions and estimated on education and learning, teach-learning strategies, scenes of teach-learning and possibility and limits in the application of the strategies. The analysis and discussion of results, had allowed to know the professor who, in its majority: are women, they follow exclusively the teaching profession, and work like hourly employee. The teaching time varies between 6 and 24 years. Barely two professors are doctors, four have master degree and one specialist. The interviwee perceive the teaching identity as fruit of the experiences that construct throughout their trajectories, influenced for personal and group issues. All professors considered relevant a good professional performance, have the rule over the area of knowledge in geriatry and gerontology, be able to use compatible education strategies with the characteristics of this curricular component;be engaged with the student independence and intellectual, teaching motivation and be fond of the area.The data show us that the searched professors follow the teaching in diverse scenes: classroom, ambulatory, hospitals, centers of sociability and health basic units; what it is presented as a possibility to integrate knowledge and approach the students to the different health area contexts, considering the insertion in the Unified Health System (UHS). Also they use a diversity of strategies from among appear: dialogued descriptive class, readings and research, studies of case and the dramatization associates to render a problem as area of class development. The investigated professors had demonstrated to be worried in knowing the expectations of the students and also using their previous experiences turn education into a most significant and stir them up responsible in the pursuit of knowledge. All the professors had been placed as facilitator of this process using the dialogue as instigator of teach-learning process tending to an integral formation of their students.